Inter‐cultural contexts: Exploring the experience of indigenous employees in mainstream Australian organisations. (12th March 2020) - Steel, Lara; Heritage, Brody
Abstract: Objective: This study aimed to understand more about the experiences of Indigenous employees within mainstream Australian workplaces. Employment and retention rates for Indigenous employees continue to be disproportionately lower than the mainstream Australian population. The potential impact of the inter‐cultural workplace context has featured little in the current research and public discourse on employment and retention rates. This study contributes further research and practice implications within the inter‐cultural and organisational psychology literature. Method: This qualitative study investigated the experiences of 10 Indigenous participants in a metropolitan area who are, or have been, employed in mainstream Australian workplaces. In‐depth interviews were conducted using grounded theory methodology and participants' responses coded to identify themes. Results: Results suggested that some Indigenous employees experience mainstream workplaces as inter‐culturally complex environments. This setting is also found to present an increased range of psychosocial barriers to successful employment and retention. A working theory of inter‐cultural code‐switching between mainstream and minority groups is proposed. Conclusion: The inter‐cultural environment of mainstream Australian workplaces may be requiring Indigenous employees to display high levels of cultural agility to achieve successful employment and retention outcomes. The implications of this study suggest that widespread government initiatives to increase Indigenous employment are unlikely to result in sustained increases in employment and retention unless inter‐cultural considerations are given due attention.